Study the Ability of Pseudomonas Aeruginosa Isolated from Different Clinical Cases to Biofilm Formation and Detection of Algd Gene - Hussamsalah al-deen; Suaad Khalil Ibrahim (Institute of Medico-legal Publications Pvt Ltd, 2022)
98 samples were collected from various clinical sources included ( Burns, wounds, urines, sputums, blood ) From the city of Baghdad , After performing the biochemical and microscopic examination, 52 isolates were obtained for Pseudomonas aeruginosa , 17 (32.7 %) isolates from burn infection , 12( 23% ) isolates from Wound infection 11 ( 21.2 % ) isolates from urine infection , 7 ( 13.5 % ) isolates of sputum and 5 ( 9.6 %) isolates from blood . Bacteria susceptibility to form biofilm has been detectedby microtiter plate method, The results showed that 80 % of the bacterial isolates were produced the biofilm with different proportions , alg D gene ( alginate production ) has been detected by polymerase chain reaction ( PCR ) Which plays an essential role in the formation of the biofilm , The PCR results showed that the percentage of gene presence was( 95.4 % )